Efficient synthesis of potent anti-tubercular drug candidate BM212 - More, N. A.; Patil, M. D.; Garud, D. R.; Gajbhiye, J. M. (Rasayan Journal of Chemistry, 2016)
A novel five step total synthesis route for an anti-tubercular drug BM212 starting from 4-chlorophenacyl bromide was developed with 48% overall yield. The synthesis is amiable for the synthesis of biologically active derivatives of BM 212.